In pursuit of socially just pedagogies in differently positioned South African higher education institutions - Leibowitz, B. (South African Journal of Higher Education, 2016)
This article concerns itself with socially just pedagogies in South African higher education. It outlines key elements of new materialist and socio-materialist views on education, and how these views portray knowledge and learning. It briefly outlines what socially just pedagogies in higher education might mean within this worldview. The data on which the study is based comprise interview transcripts with ten lecturers at each of two higher education institutions one historically advantaged and one historically disadvantaged, in the South African historical and political context. The transcripts are discussed as an encounter between the author and the data, with an emphasis on those elements that produce and affective reaction. Institutional influence is discussed in relation to assemblages including: dimensions of space, time, discourse on teaching and learning, and material artefacts. The article concludes with a consideration of what agency, responsibility and freedom might entail under these conditions.